Effect of Pyramid Enzyme on the Performance of Finishing Cattle Fed Sorghum-based Diets - Elizabeth R. Kiselewski (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: The objective of this study was to investigate the effects of adding Pyramid PowerGrower Ruminant to sorghum-based finishing diets to assess the effect on diet digestion, feedlot performance, and carcass characteristics. Study Description: Crossbred steers (n = 280; body weight = 974 lb ± 33.5) were randomly allocated to 36 feedlot pens containing seven (eight pens) or eight (28 pens) animals per pen. At the initiation of the study, steers were vaccinated for viral (Pyramid 5 + Presponse SQ, Boehringer Ingelheim, Duluth, GA) and clostridial (Bovilis Covexin 8; Merck Animal Health, Rahway, NJ) pathogens and treated for internal and external parasites Cydectin (Elanco Animal Health, Indianapolis, IN), and with Draxxin (Zoetis Animal Health, Florham Park, NJ) as a prophylactic. Steers were implanted with Synovex One Feedlot (Zoetis Animal Health, Florham Park, NJ), and received an oral drench of Lactipro (MS Biotec, Wamego, KS). Finishing diets consisted of 59.62% ground sorghum, 25% sorghum-based dried distillers grains with solubles, 12% corn silage, and 3.35% supplement. Treatments consisted of diets with or without added enzyme, and the enzyme treatment provided 1.5 lb of enzyme concentrate per ton of complete feed (86% dry matter basis; Pyramid PowerGrower Ruminant; Pyramid Feeds, Scott City, KS). Cattle were fed once daily, ad libitum. After 148 days on feed, steers were transported to a commercial abattoir in Holcomb, KS. Performance measurements included dry matter intake, average daily gain, and feed:gain ratio. On the day of harvest, hot carcass weight and incidence of liver abscesses were assessed. After a refrigeration period of 96 hours, carcass characteristics, including ribeye area, marbling score, 12th rib fat thickness, and U.S Department of Agriculture quality and yield grade, were determined. Nutrient digestibility was determined using acid detergent insoluble ash as an internal marker, and was calculated as: Effect of Pyramid PowerGrower Ruminant on feedlot performance and diet digestibility. The Bottom Line: Adding Pyramid PowerGrower Ruminant enzyme mix to sorghum-based finishing diets resulted in modest, but nonsignificant, improvements in diet digestibility, feedlot performance, and carcass weight.
Keywords: enzyme; cattle; sorghum